A dialogic reading instruction involving ESL undergraduates / Diog Dios - Dios, Diog (2010)
The study aimed to investigate the use of Dialogic Reading Instruction (DRI) for teaching academic reading. The study was intended only to introduce the use of DRI and not to assess the impact of DRI on the students' reading performance. It started with one DRI session early in the semester and subsequently another session a month after. DRI was conducted in the academic reading lesson involving 20 student participants. The students were from the Bachelor of Administrative programme, selected based on convenience sampling. At the end of the two separate lessons the students were instructed to fill up a likert-type questionnaire on their perception of the use of DRI. Out of 20, five students were selected at random for semi-structured interviews to find out the views of the students as regards the use of DRI. The study found that the students were very responsive to the use of DRI. Those interviewed also related their experience positively, implying that they were in strong favour of the use of DRI for academic reading.